A longitudinal study examining uptake of new recreation infrastructure by inactive adults - Ben J. Smith; Ruth MacKenzie-Stewart; Fiona J. Newton; Tilahun N. Haregu; Adrian Bauman; Robert J. Donovan; Ajay Mahal; Michael T. Ewing; Joshua D. Newton (BMC, 2019)
Abstract Background The built environment is reported to influence physical activity in populations, but longitudinal evidence about the impact of building new physical activity infrastructure is limited. This study aimed to prospectively investigate the uptake and usage of the newly established Peninsula Aquatic and Recreation Centre (PARC), a large multi-purpose recreation facility in Melbourne, Australia. Methods Physically inactive adults (n = 549) from the City of Frankston were recruited before the opening of PARC and followed up 12 months later to measure frequency of attendance at the Centre, and the purposes and barriers to use. Multivariable methods were used to identity the demographic, cognitive and social predictors of attendance, and the relationship between PARC use and improvements in leisure-time physical activity. Results Over 12 months 8.7% of the sampled residents used PARC once per month or more, 17.5% attended less than once per month, and 73.8% did not use the Centre. Lap swimming was the dominant purpose for attendance, and the major barriers were cost of transport and cost of entry. Independent predictors of usage were being female, having children, living within 5 km of the Centre, and expressing strong intentions for use prior to its opening. Use of PARC was not associated with progression to a higher level of total leisure-time physical activity. Conclusions While installation of multi-purpose aquatic and recreation facilities may be considered an investment towards physical activity in populations, regular use by inactive people is likely to be low. Strategies to reduce barriers, including cost and transport, and to motivate use should be trialled in order to improve the public health impacts of this form of infrastructure.